2017
DOI: 10.1111/dom.12980
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baseline glycated haemoglobin, diabetes duration and body mass index on clinical outcomes in the LixiLan‐O trial testing a titratable fixed‐ratio combination of insulin glargine/lixisenatide (iGlarLixi) vs insulin glargine and lixisenatide monocomponents

Abstract: To determine whether baseline characteristics had an impact on clinical outcomes in the LixiLan‐O trial (N = 1170), we compared the efficacy and safety of iGlarLixi, a titratable fixed‐ratio combination of insulin glargine 100 U (iGlar) and lixisenatide (Lixi) with iGlar or Lixi alone in patients with uncontrolled type 2 diabetes mellitus (T2DM) on oral therapy. Subgroups according to baseline glycated haemoglobin (HbA1c; <8% or ≥8% [<64 or ≥64 mmol/mol]), T2DM disease duration (<7 or ≥7 years) and body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 11 publications
5
23
0
1
Order By: Relevance
“…The findings of the subgroup analyses in the Japanese population are consistent with those of the global LixiLan trials, 33 which found that iGlarLixi was effective across key baseline subgroups, including populations that may be challenging to treat (e.g., elderly people and those with high baseline BMI).…”
Section: T a B L E 3 Hba1c And Hypoglycaemia Outcomes By Baseline Hba1csupporting
confidence: 79%
“…The findings of the subgroup analyses in the Japanese population are consistent with those of the global LixiLan trials, 33 which found that iGlarLixi was effective across key baseline subgroups, including populations that may be challenging to treat (e.g., elderly people and those with high baseline BMI).…”
Section: T a B L E 3 Hba1c And Hypoglycaemia Outcomes By Baseline Hba1csupporting
confidence: 79%
“…The results of an exploratory analysis of the LixiLan-L study showed that iGlarLixi provided consistent improvements in glycemic control, and mitigated (up to − 0.9 kg) the gain in body weight observed with iGlar (up to + 1.1 kg), regardless of HbA1c subgroup (< 8%, ≥ 8%), duration of T2D (< 10, ≥ 10 years), or body mass index (< 30, ≥ 30 kg/m 2 ) [95]. Similar results have been reported from a post hoc analysis of the LixiLan-O study [107], which are further supported by a recently published analysis demonstrating superior glycemic control with iGlarLixi compared with iGlar or lixisenatide in patients with a baseline HbA1c ≥ 9%, with reductions in HbA1c of − 2.9%, − 2.5%, and − 1.7% for iGlarLixi, iGlar, and lixisenatide, respectively [108]. The results of another post hoc analysis of the LixiLan-L study showed that reductions in HbA1c to week 30 were greater for iGlarLixi than iGlar, irrespective of screening HbA1c subgroup (≤ 8%: − 1.1 vs. − 0.5; < 8% to ≤ 9%: − 1.4 vs. − 1.0; > 9%: − 2.4 vs. − 1.8; all p < 0.0001).…”
Section: Fixed-ratio Combination Of Insulin Glargine 100 Units/ml Andsupporting
confidence: 66%
“…Mean body weight decreased in iGlarLixi recipients but increased in insulin glargine recipients (between‐group difference, 1.4 kg; P < 0.0001), and the number of hypoglycaemic events was similar in the two groups 53. In both studies, the improvement in glycaemic control with iGlarLixi vs the individual therapies was consistent regardless of baseline HbA 1c , BMI or diabetes duration 54, 55.…”
Section: Fixed‐ratio Formulationsmentioning
confidence: 80%